Front Cover: Identifying Different Halogen‐/Hydrogen‐Bonding Interaction Modes in Binary Systems that Contain an Acetate Ionic Liquid and Various Halobenzenes (ChemPhysChem 9/2018). Issue 9 (17th April 2018) - Xu, Jing; Zhou, Yu; Deng, Geng; Ashraf, Hamad; Yu, Zhi‐Wu
Abstract : The Front Cover illustrates the different patterns of excess spectra (multi‐/two‐state) in the binary systems containing C6 F5 I/C6 F5 Br and the acetate‐based ionic liquid. They show different interaction modes and provide information on the existing species in the systems, helping to understand the solubility property of halogenated drug molecules in ionic liquids. More information can be found in the Article by J. Xu et al. onpage 1030 in Issue 9, 2018 (DOI:10.1002/cphc.201701302 ).